Evaluation of the cardiorespiratory and antinociceptive effects of the total intravenous anesthesia technique with xylazine-butorphanol-propofol compared to isoflurane in calves under experimental laparotomy - Sato, Shogo; Kanno, Chihiro; Matsuura, Akihiro; Maeda, Yosuke; Takahashi, Fumiaki (Frontiers in Veterinary Science, 2025)
A novel total intravenous anesthesia (TIVA) technique combining xylazine (0.1 mg/mL), butorphanol (0.01 mg/mL), and propofol (2 mg/mL) in a 5% dextrose solution (XBP) has shown promising results in calves. In the present study, we compared XBP-TIVA with isoflurane (ISO) inhalation anesthesia during experimental laparotomy in calves, evaluating cardiorespiratory and antinociceptive effects. Fourteen clinically healthy male and female calves (body weight: 28.5–155.0 kg; age: 17–186 days) were randomly assigned to receive XBP-TIVA (continuous infusion at a rate of 6 mL/kg/h) or ISO inhalation anesthesia (end-tidal concentration: 1.3 ± 0.1%) for 60 min during laparotomy. We measured rectal temperature (RT), heart rate (HR), arterial blood pressure, and arterial blood gas values. Then, HR variability (HRV) components and stress hormones were measured to analyze autonomic nervous system and neuroendocrine responses to nociceptive stimuli. Measurements were taken before drug administration (baseline) and at 5-min or 15-min intervals after anesthesia maintenance. Nociceptive stimuli were administered, including skin and muscle incision, intestinal manipulation, muscle suture, and skin suture. The statistical significance level was set at p < 0.05. The XBP group maintained significantly higher RT throughout anesthesia. HR decreased significantly from baseline in both groups. Mean arterial pressure remained significantly higher in the XBP group. The XBP group demonstrated significantly lower arterial partial pressure of carbon dioxide values than the ISO group throughout anesthesia maintenance. During intestinal manipulation, the normalized high-frequency component significantly decreased while the low-frequency/high-frequency ratio significantly increased. Norepinephrine concentrations in both groups demonstrated a significant decrease from baseline values prior to the nociceptive stimuli; however, the difference disappeared during and before the stimulus. Epinephrine concentrations were lower than baseline values at all measurement points in both groups; however, a significant increase from before to after the nociceptive stimulus was observed only in the ISO group. In conclusion, compared to ISO anesthesia, XBP-TIVA maintained superior cardiorespiratory stability, higher RT, and more efficient ventilation. XBP demonstrated superior nociceptive suppression, though both protocols suggested sympathetic responses to visceral pain. These findings suggest that XBP-TIVA may be a safe, effective, and potentially superior alternative to isoflurane inhalation anesthesia for surgical procedures in calves.